European Legislation and Politics as Seen by Former Members of the European Parliament - Alfredo De Feo; Michael Shackleton (Rechtsgeschichte - Legal History)
This article is based on the oral interviews that Members of the European Parliament (EP) from 1979 to 2019 have deposited at the Historical Archives of the EU (HAEU) and that are freely available to researchers.Their memories inspired us to focus on some speciﬁc features that are, in our view, relevant to the evolution and development of the European Parliament. In the forty years from 1979 to 2019 the EP completely changed its role: from mere discussion forum to co-legislator. Many manuals give an excellent and complete overview of formal and informal EP powers. This is not the aim of this article. Our ambition is to raise curiosity and interest sufficiently for readers to visit the HAEU website and to listen to some of the interviews.